ANALISIS PENGARUH UTANG LUAR NEGERI DAN RISIKO NEGARA TERHADAP CAPITAL FLIGHT DI NEGARA BERKEMBANG ASEAN - Rt. Ainun Lutfiah; Vadilla Mutia Zahara; Cep Jandi Anwar (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
This study aims to analyze the effect of foreign debt and country risk on capital flight in ASEAN developing countries. The country's risks include the current account/export ratio, economic growth, inflation, and political instability. Determination of the sample is based on annual time-series data for the period 2005 to 2019. The data used in this study is secondary data from the World Bank 2021 and the World Governance Indicator (WGI) 2021. This study uses panel data regression analysis with Fixed Effect Model using cross-section SUR (Seemingly Unrelated Regression). Based on the results of the F statistical test (simultaneous test) shows that foreign debt, current account/export ratio, economic growth, inflation, and political instability simultaneously have a significant effect on capital flight in ASEAN developing countries from 2005 to 2019. Then, based on the results t statistical test (partial test) shows that foreign debt, economic growth, inflation, and political instability have a significant positive effect on capital flight, while the current account/export ratio has a significant negative effect on capital flight in ASEAN developing countries from 2005 to 2019